PENGARUH JOB DESK, DISIPLIN DAN PELATIHAN TERHADAP KINERJA KARYAWAN PADA PT BPR DANA FANINDO KOTA BATAM - juniati; Suhardi, Suhardi (SCIENTIA JOURNAL, 2025)
This research aims to analyze the influence of job descriptions, work discipline, and training on employee performance. Data was collected through questionnaires distributed to 108 employees. Data analysis used multiple linear regression with SPSS assistance. The results showed that job descriptions, discipline, and training has a positive and significant effect on employee performance. Simultaneously, these three independent variables contributed significantly to employee performance variables. This research recommends the importance of clear job descriptions, improved work discipline, and continuous training programs to enhance employee performance. Keywords: Job Description, Discipline, Training, Empolyee Performance